Domestic Market Fragmentation and Economic Growth in China - Sandra Poncet (European Regional Science Association (ERSA), 2003)
This paper analyses the relationship between domestic market fragmentation and economic performance at the sub-national level within China. Market segmentation means that goods, services and factors of production -capital and labour- are not easily mobile across different regions. China's political and economic structure is described as de facto federalism. It is traditionally based on a decentralized regional planning where provinces can be considered as autonomous economic actors that govern most economic activities and have huge regulatory, economic and financial powers in hands. The paper follows a two-step procedure. First, it estimates a province-level indicator of market fragmentation based on a price-based approach. Specifically we focus on observed deviations from the Law of One Price for a set of homogeneous agricultural products. We argue that inter-regional price volatility in integrated economies should not depend on the relative position of markets. We use a three-dimensional data set of monthly prices on 7 agricultural goods, between 1987 and 1997 across 170 cities of 28 provinces. We deem a province to be poorly integrated when inter-market price dispersion is greater for markets that lie on different side of its border than for markets that locate within the province, after distance is controlled for. Second, it then embeds this measure of market fragmentation into a cross-province growth framework, estimated with the GMM-system method. Results underline the economic importance of the Chinese provincial borders to be substantial as they are significant explanatory variables in accounting for observed deviations of the Law of One Price. Controlling for distance, markets on opposite sides of regional borders feature substantially higher differences in commodity prices than do cities on either side of the border. There is no evidence of declining trend in market segmentation between Chinese provinces. The evolution of the border effect over time is consistent with the changing fortunes of the reforms in China. Market integration does not seem to have much improved over the reform process at least until 1995. Our analysis of provincial growth dynamics underlines the favourable impact of market integration on economic performance and agricultural output. Our indicator of market fragmentation enters negatively in all regressions. Its coefficient is not only significant but also proves very robust to the inclusion of control variables such as inflation, trade openness and the importance of the non-public sector. The larger a province's border effect (thus the lower its economic integration with the rest of the country), the lower its economic growth. These findings prove the detrimental impact of market segmentation on growth in China. By extension, it underlines the counter-productive effect of protectionist policies adopted by provincial authorities along the reform course.
Keywords: 330